A Combined Intervention of Zinc, Multiple Micronutrients, and Albendazole Does Not Ameliorate Environmental Enteric Dysfunction or Stunting in Rural Malawian Children in a Double-Blind Randomized Controlled Trial. Issue 1 (2nd November 2016) - Wang, Alfred Z; Shulman, Robert J; Crocker, Audrey H; Thakwalakwa, Chrissie; Maleta, Kenneth M; Devaraj, Sridevi; Manary, Mark J; Trehan, Indi
Abstract: Background: Environmental enteric dysfunction (EED) and linear growth stunting affect many rural agrarian children in the developing world and contribute to the persistently high rates of stunting that are observed worldwide. Effective interventions to consistently ameliorate EED are lacking. Objective: We tested whether a bundle of safe and affordable interventions would decrease EED and stunting over 12–24 wk in a cohort of rural Malawian children 12–35 mo old. Methods: This was a randomized, double-blind, placebo-controlled clinical trial in which the intervention group received a single dose of albendazole and 14 d of zinc at enrollment and after 20 wk. The intervention group also received a daily multiple micronutrient powder throughout the 24 wk of study. The primary outcomes were improvements in EED, as measured by the urinary lactulose-to-mannitol ratio (L:M ratio) from dual-sugar absorption testing, and linear growth. Urinary L:M ratios and anthropometric measurements were evaluated after 12 and 24 wk of intervention and compared with a placebo group that did not receive any of these interventions. Results: A total of 254 children were enrolled at a mean age of 24 mo; 55% were female. Their mean weight-for-age z score was −1.5, and their mean length-for-age z score was −0.9. After 12 and 24 wk of study, increases in the L:M ratio did not differ between the intervention group (0.071 and 0.088 units, respectively) and the placebo group (0.073 and 0.080 units, respectively) ( P = 0.87 and 0.19, respectively). Relative changes in length and weight also did not differ significantly between groups at any time point. Conclusion: The combined usage of albendazole, zinc, and a daily multiple micronutrient powder did not decrease EED or stunting in this population of agrarian children 12–35 mo old in rural Malawi. Alternative interventions to improve these diseases should be investigated. This trial was registered at clinicaltrials.gov as NCT02253095.